Prevalence of amyloid transthyretin cardiomyopathy in elderly subjects from the general population: first results from the CATCH study. (3rd October 2022) - Aimo, A; Vergaro, G; Moscardini, S; Puccianti, D; Castiglione, V; Gentile, F; Fabiani, I; Barison, A; Agazio, A; Picerni, A; Poggianti, E; Taddei, C; et al.
Abstract: Background: Amyloid transthyretin cardiomyopathy (ATTR-CM) has become treatable. Wild-type ATTR-CM is an age-related disorder. Establishing the exact prevalence of ATTR-CM in elderly subjects from the general population may be useful for healthcare providers and policy makers alike. Methods: The Characterizing the burden of Amyloid Transthyretin CardiomyopatHy in the elderly (CATCH) study is a population screening on all subjects aged ≥65 years followed by general practitioners working in a part of Tuscany (Italy) where there is no cluster of variant ATTR. The study started on March 12, 2021 and is ongoing. The first step of the evaluation includes clinical history and physical examination, electrocardiogram, transthoracic echocardiogram, and blood sampling with measurement of N-terminal pro-B-type natriuretic peptide and high-sensitivity (hs) troponin T. The following elements are searched: 1) any clinical red flag of amyloidosis (history of carpal tunnel syndrome, lumbar spine stenosis, etc.), 2) interventricular septal thickness ≥12 mm or other echocardiographic red flags, 3) hs-troponin T higher than the upper reference limit (14 ng/L). Patients with any of these elements are referred to a second step including diphosphonate scintigraphy and the search for a monoclonal protein in the serum and urine. The standard diagnostic workup for CA is then followed until the diagnosis is confirmed or discarded. Results: As of October 13, 2021, 514 subjects ≥65 years have been evaluated for possible participation. Among them, 135 (26%) could not be contacted, were reluctant to enter the study, died before being contacted, or were bedridden. Out of the other 379 subjects, 329 (87%) have already undergone the first step. Forty percent of individuals (n=132) have been referred to the second step. Thirteen subjects have declined (10%); 69 patients have undergone diphosphonate scintigraphy and the search for a monoclonal protein (while the other 50 are awaiting these exams). Two subjects showed an intense myocardial uptake of the diphosphonate tracer (Perugini score 2–3) and no monoclonal protein, and were then diagnosed with ATTR-CM. They were both women, aged 83 and 78 years, both mildly symptomatic for dyspnea (New York Heart Association II) and with unexplained hypertrophy. The search for TTR gene mutation was negative in the first case and is still ongoing in the second. Based on these preliminary data, the prevalence of ATTR-CM in the elderly population can be calculated as 2/266=0.8% (Figure 1). Conclusions: The CATCH study is expected to enroll at least 1, 000 subjects and will provide the first data on the epidemiology of ATTR-CM in elderly subjects. Based on an interim analysis, almost 1 in 100 individuals ≥65 years has ATTR-CM. Funding Acknowledgement: Type of funding sources: None.